PENEGAKAN HUKUM TERHADAP PELAKU TIFNDAK PIDANA MEMBUJUK ANAK DI BAWAH UMUR UNTUK MELAKUKAN PERBUATAN CABUL TERUS MENERUS - S. Endang; Zainudin Hasan; Raisa Amanda Aurelia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
Abstract Sexual harassment is undesirable and unwanted sexual behavior or sexual interest that reasons soreness to the recipient of the harassment while the author's findings, based totally on expert reasoning, have proved legally and convincingly that he devoted the crime of inducing a minor to dedicate himself to preserve to have interaction in pornographic activity underneath section seventy six E Jo segment 82(1) of Act No. 35 of 2014 and situation to criminal penalties under infant protection Act No. 23 of 2002 2nd change to emerge as Jo Act section 64(1) of the criminal Code. consequently, the accused shall serve 4 years imprisonment at LPKA magnificence II Bandar Lampung in Masgar and 4 months education at LPKS Insani Berguna Pesawaran.